Immigration an Globalisation from Below: The Case of Ethnic Restaurants in Lisbon. - Fonseca, Lucinda; Malheiros, Jorge (Finisterra, 2004)
This paper aims to analyse the role of immigrants in the processof economic restructuring and secondary internationalisation of the metropolises in opposition to the hegemonic globalisation process associated to Transnational Corporations (TNC) and its strategies. This will be illustrated with a comparative reading of the diffusion process of ethnic restaurants (Chinese and Indian) and franchised pizza and hamburger (McDonald’s, Pizza Hut) outlets in Lisbon.